Management of Colletotrichum leaf spot of turmeric through fungicides - V P Pandey, R S Mishra, (Journal of Spices and Aromatic Crops, 2015)
The major foliar diseases of turmeric (Curcuma longa L.) reported in Uttar Pradesh are leaf spot caused by Colletotrichum capsici and leaf blotch caused by Taphrina maculans. Leaf spot generally appears in September and October, which can reduce rhizome yield upto 62.5%. Therefore, the experiment was conducted to evaluate the efficacy of four fungicides viz., Hexaconazole (0.1%), Propiconazole (0.1%), Tricyclazole (0.1%) and Carbendazim + Mancozeb (0.1%) for the management of leaf spot disease of turmeric through rhizome treatment + foliar spray and foliar spray alone at 45 and 90 days after planting (DAP). Rhizome treatment with Carbendazim + Mancozeb (0.1%) gave the best results for rhizome germination (91.13%) followed by Propiconazole (88.40%) and Hexaconazole (87.30). Foliar application of Propiconazole (0.1%) at 45 and 90 DAP was significantly superior in minimizing percent disease intensity (27.61 PDI) in comparison to foliar spray + rhizome treatment with Hexaconazole (28.50 PDI) and Tricyclazole (33.73 PDI). The fresh rhizome yield ranged from 33.96 - 34.33 t ha-1 with Propiconazole and 31.15 - 33.22 t ha-1 with Hexaconazole as compared to the control (28.17 t ha-1). C: B ratio was found to be highest (1:2.65) with foliar spray of Propiconazole.